Dimensions of Moral Agency. - Boersema, David (Cambridge Scholars Publishing, 2014)
Dimensions of Moral Agency addresses and exemplifies the multi-dimensionality of modern moral philosophy. The book is a collection of papers originally presented at the Northwest Philosophy Conference in October 2013. The papers encompass a wide variety of topics within moral philosophy, including metaethics, normative ethics, and applied ethics, and broadly fall within the areas of the nature of moral agency and moral agency as it is played out in particular aspects of people's lived experie ...